Modern Smallholders: Creating Diversified Livelihoods and Landscapes in Indonesia - Race, Digby; Suka, Aneka Prawesti; Oktalina, Silvi Nur; Bisjoe, Achmad Rizal; Muin, Nurhaedah; Arianti, Novita (Springer, 2022)
Encouraging smallholders to diversify their livelihoods has been a long-held policy objective of many governments to create resilient rural communities that can cope with seasonal variations in food production and price fluctuations in commercial markets. Due to the dynamic nature of smallholders’ livelihoods, the relative contribution of different sources to household income often remains unclear. Recent research in Indonesia used a household survey of a stratified sample of smallholders (n = 240) in eight villages (five districts) to obtain data of smallholders’ income and the relative importance of agroforestry. The research analysed income data from the same households (80) collected in 2013, 2017 and 2020, providing longitudinal data of livelihoods and household income. Results revealed important information about the nature of Indonesia’s rural economy, whereby many smallholders received most of their income from off-farm sources (56 of income). While most smallholders still reported farming as their primary occupation, their families’ livelihoods are diverse and mainly supported by non-farm enterprises. Even the mix of farming enterprises is evolving, with agroforestry a prominent land-use and source of household income in Indonesia (29 of income), indicating that smallholders are intentionally diversifying their land-use and livelihoods. Our research found that conventional agricultural enterprises generated just 14 of household income, yet remains vital for household food security. The high proportion of off-farm income for smallholders has important implications for land management and rural development across Indonesia, as smallholders forgo intensification of their farming systems and instead opt for diversification—and at scale, creating resilient landscapes and livelihoods. © 2021, Steve Harrison, John Herbohn.